(untitled) (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2024)
This research investigates the impact of job embeddedness on Saudi female nurses’ intention to leave their jobs and the nursing profession entirely. Using established quantitative measures along with the validated measure of family embeddedness by (Alkothami, 2016), 684 Saudi female nurses participated in this research. The results of hierarchal regression analysis support the negative relationship between organisational and family embeddedness and Saudi Arabian female nurses’ turnover intentions. The implication of these results is presented in relation to Saudi healthcare organisation.